Idiopathic scoliosis and balance - Kovačević, Milena D; Đelić, Marina; Krasnik, Rastislava (Medicinski podmladak, 2024)
Idiopathic scoliosis (IS) is a three-dimensional deformity of the spine and the trunk, of unknown etiology. Balance or postural control can be defined as the ability to maintain the body’s line of gravity above the base of support and thus to avoid falling. Adequate balance control is not only important for maintaining postural stability, but also for safe mobility during activities of daily life. This requires efficient central processing of information coming from the visual, vestibular and somatosensory (proprioceptive) systems. Some studies showed that people with idiopathic scoliosis have reduced postural stability, assessed with posturography, as well as proprioceptive and vestibular deficits. Two hypothesis in the literature, biomechanical and sensory integration hypothesis, tried to explain this from different point of view. The biomechanical hypothesis emphasizes biomechanical and morphological changes in IS as responsible for poorer postural stability, while the hypothesis of sensory integration points out that certain people with idiopathic scoliosis have impaired dynamic regulation of sensorimotor integration due to an inaccurate evaluation of sensory inputs. Studies that used clinical balance tests showed difficulties in medio-lateral stability and dynamic proprioception in IS. Further studies on balance in this population are needed to deepen knowledge in this area. Key words: scoliosis, postural balance, proprioception